ChemInform Abstract: Tuning the Mn and Fe Valence States into New Ca0.7Mn2‐xFexO4 (0 < x ≤ 0.60) Solid Solution During Reversible Redox Processes. Issue 40 (September 2016) - Lesturgez, Stephanie; Goglio, Graziella; Duttine, Mathieu; Wattiaux, Alain; Durand, Etienne; Hernandez, Julien; Majimel, Jerome; Demourgues, Alain
Abstract: Ca0.7 Mn2‐x Fex O4 (x = 0—0.6) with Mn 4+ amounts varying from 33% to 43% are prepared by an aqueous self‐combustion route involving stoichiometric mixtures of Ca, Mn, and Fe nitrates with powdered glycine in a 1:2 molar ratio (hot plate in stainless steel beaker, 220 °C) followed by firing the resultant ashes in air (850 °C, 12 h).